PENDANPINGAN PEMBUATAN PROSES BISNIS PADA KELOMPOK PETERNAK LEBAH KLANCENG DUSUN TENGKLIK DESA KEDAWUNG KECAMATAN JUMAPOLO KABUPATEN KARANGANYAR - Didik Setyawan; Dewi Astuti Herawati; Faiz Rahman Siddiq; D. Andang Arif Wibawa; Maria Odelia Intan Eka Saputri (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Klanceng Honey has many benefits for human health. It can boost immune system, act as an antibacterial agent and can also be used as an alternative medicine for diabetes, heart disease and stroke. Klanceng Honey is pure honey made from flower nectar that does not expire. The Klanceng honey farmer group in Kedawung village, Jumapolo district, Karanganyar regency, Central Java, has been in business for almost two years but has not made any progress. The results of the problem identification showed that there is no standardization of the activities that are carried out. The purpose of this community service program is to develop a business process to achieve working standards for Klanceng honey cultivation activities. The methodology used consists of 3 stages. The first stage is to observe and identify the problems of Klanceng honey farmers. The second step is to find references that are relevant to the business processes of the Klanceng honey farmer group. The third stage was to conduct interviews to create a standard operating procedure for the Klanceng honey farmer group. These stages resulted in a business process for Klanceng honey cultivation and a standard operating procedure for Klanceng honey cultivation activities that can be fully understood by all group members.